Clinico-pathological outcomes after total parietal peritonectomy, cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in advanced serous papillary peritoneal carcinoma submitted to neoadjuvant systemic chemotherapy- largest single institute experience. Issue 11 (November 2019) - Deraco, Marcello; Sinukumar, Snita; Salcedo-Hernández, Rosa Angélica; Rajendra, Vinayakumar J.; Baratti, Dario; Guaglio, Marcello; Nizri, Eran; Kusamura, Shigeki
Abstract: Introduction: Serous papillary peritoneal carcinoma (SPPC) is a rare clinical entity. Based on the understanding of the pattern of spread, its multifocality, polyclonality and the high frequency of diffuse, widespread peritoneal metastasis, a robust rationale for cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) for SPPC exists. Herein we report the clinical outcomes of SPPC patients treated with neoadjuvant systemic chemotherapy (NACT) followed by CRS including total parietal peritonectomy and HIPEC. Methods: Clinico-pathological data of 22 patients of serous papillary peritoneal carcinoma (SPPC) was retrospectively analyzed from a prospectively maintained database from June 2000 to July 2017. Patients were treated with CRS, total parietal peritonectomy and HIPEC with cisplatin (42 mg/L of perfusate) and doxorubicin (15 mg/L of perfusate) after NACT. Survival curves were calculated from the date of surgery. Results: 22 patients underwent CRS, total parietal peritonectomy and HIPEC. The median age was 62 years (Range 47–72). On histological evaluation, 18/30 (60%) parietal peritonectomy specimens showed microscopic disease, when no disease was evident macroscopically at surgical exploration. Grade III-IV surgical complications were recorded in 4/22 (18%) patients. There was no postoperative mortality. At a median follow up of 12 months, the five-year overall survival (OS) was 64.9%. The median OS was not reached. Median progression-free survival was 32.9 months and progression-free survival at 5 years was 33.2%. Conclusion: CRS with total peritonectomy + HIPEC after NACT, presents as a promising treatment modality for SPPC, and could be associated with good survival results in patients with SPPC.